Hands-On Microservices with Kubernetes : Build, Deploy, and Manage Scalable Microservices on Kubernetes. - Sayfan, Gigi (Packt Publishing, Limited, 2019)
Hands-on Microservices with Kubernetes will help you create a complete CI/CD pipeline and design and implement microservices using best practices. You will get hands on experience with the latest and greatest technologies, such as gRPC APIs, serverless frameworks, and service meshes.